A noninvasive X-ray technique for determination of liquid holdup in a rotating packed bed. (22nd December 2015) - Yang, Yucheng; Xiang, Yang; Chu, Guangwen; Zou, Haikui; Luo, Yong; Arowo, Moses; Chen, Jian-Feng
Abstract: A rotating packed bed (RPB) has received considerable attention of many researchers due to its high mass transfer rate and mixing efficiency. In order to effectively promote and employ RPB in the chemical industry, it is necessary to have a better understanding of its flow characteristics. In this study, a noninvasive X-ray technique was employed for the first time to examine the hydrodynamics of RPB. Time-average tomographic cross sectional images showing the distribution of liquid in the packing zone under various operating conditions were captured. It was observed that high rotational speed improves the distribution of liquid in the packing. Additionally, quantitative analysis based on liquid holdup was made, and the effects of rotational speed, liquid flow rate, fluid viscosity, surfactant and two different kinds of packings on liquid holdup were evaluated. Results indicate that liquid holdup decreases with an increase in rotational speed and a reduction in both liquid flow rate and liquid viscosity. However, it was observed that surfactant has no significant effect on liquid holdup. Correlations to predict liquid holdup were developed, and the calculated values are in agreement with the experimental values with deviations within ±22%. Furthermore, the mean residence time in various conditions is calculated based on liquid holdup.